A first record of bulk atmospheric deposition patterns of major ions in southern South America - Carnelos, D.A.; Portela, Silvina Isabel; Jobbagy Gampel, Esteban Gabriel; Jackson, R.B.; Di Bella, Carlos Marcelo; Panario, D.; Fagúndez, C.; Piñeiro Guerra, J.M.; Grion, L.; Piñeiro, G. (Springer, 2019)
Despite the importance of long-term atmospheric deposition of ions for vegetation productivity and biogeochemistry, southern South America lacks long-term deposition records. We report a 6-year-long record of atmospheric deposition measurements of Mg2+, Ca2+, Na+, K+, Cl−, SO42−, NO3− and NH4+ in the plains of southern South America, which encompass one of the most important agricultural basins and urban clusters of the continent. After establishing a deposition measurement network across four sites in Argentina and Uruguay, we collected bulk atmospheric deposition monthly form January 2007 through December 2012 in an east–west transect of 700 km. Spatial changes in the sea-salt component of atmospheric deposition were primarily associated with proximity to the sea—as observed in other regions of the world—whereas non-sea-salt components of atmospheric deposition of terrestrial origin were primarily associated with the size of the human population surrounding collection sites. Atmospheric deposition showed a strong interannual variability (CV 50%) mainly associated with variations in the non-sea salt components of terrestrial origin and were within observed values for other relatively unpolluted sites of South America and globally. However, atmospheric deposition appears to be increasing in the region, particularly for SO42− and other ions around Buenos Aires, Argentina, which may represent an early warning of increased air pollution in the area. Average annual regional deposition of sulfate (SO42−) was 12.7 kg S hectare−1 and nitrate (NO3−) was 9.2 kg N hectare−1. Weighted average concentrations of base cations (sum of Mg2+, Ca2+, Na+ and K+) was 0.27 mg L−1, and weighted average concentrations of SO42−, NO3− and NH4+ were 0.094, 0.018 and 0.046 mg L−1, respectively. Our work highlights the need for long-term networks recording atmospheric deposition in the region, increasing knowledge of nutrient cycling and establishing a baseline for future atmospheric pollution measurements.